Discrete emotions linking abusive supervision to employee intention and behavior - Peng, Ann Chunyan (2020)
Drawing on appraisal theories of discrete emotions, we propose and test a model in which abusive supervision directed toward oneself and toward work unit peers (coworker abusive supervision) are interactively related to generalized feelings of shame, anger, and fear. These discrete emotions, in turn, tend to precipitate distinct responses that do not directly target the supervisor. We tested our hypotheses with a three-wave, time-lagged survey of 285 full-time workers from 55 work units. Consistent with our theorizing, supervisory abuse was associated with stronger feelings of shame while at work when the abusive supervision reported by one's coworkers was lower (vs. higher), whereas abuse had a stronger association with anger when coworkers also perceived relatively high levels of abuse. The distinct action tendencies associated with shame and anger are related to employees engaging in less voice behavior and more interpersonal deviance, respectively, and fear is related to higher turnover intentions. We discuss the study's implications for theory development concerning abusive supervision.